A Chaos-Based Image Encryption Scheme Using the Hamming Distance and DNA Sequence Operation - Sha, Yuwen; Bu, Fanling; Jahanshahi, Hadi; Wang, Linian (Frontiers in Physics, 2022)
In this paper, we introduced a new memristive chaotic system with the rich dynamic behavior, and then we proposed a chaotic-based image encryption scheme based on permutation-confusion-substitution structure. In our scheme, the Hamming distance is used to design a plain-related chaotic system initial condition, and the generated chaotic sequences are assigned to permutation, diffusion and substitution stages. In permutation stage, an effect pixel confusion is implemented through a new permutation approach, which is a double-ended select-swap scrambling strategy. In diffusion stage, DNA XOR operation is implemented followed by DNA triploid mutation is introduced so as to enhance the strength of our encryption system. A number of experiments and extensive safety analysis have been carried out and the results fully justify that our scheme not only ensures desirable security but also has superior efficiency.